2021
DOI: 10.1016/j.jbc.2021.101096
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional epithelial–mesenchymal crosstalk provides self-sustaining profibrotic signals in pulmonary fibrosis

Abstract: Idiopathic pulmonary fibrosis (IPF) is the prototypic progressive fibrotic lung disease with a median survival of 2 to 4 years. Injury to and/or dysfunction of the alveolar epithelium is strongly implicated in IPF disease initiation, but the factors that determine whether fibrosis progresses rather than normal tissue repair occurs remain poorly understood. We previously demonstrated that zinc finger E-box-binding homeobox 1–mediated epithelial–mesenchymal transition in human alveolar epithelial type II (ATII) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 60 publications
0
24
0
Order By: Relevance
“…To investigate common regulators of PLOD2 and LOXL2 in lung fibrosis, we studied their expression in primary human lung fibroblasts over a 72-hr time course following activation ( Figure 2—figure supplement 1a ) of transforming growth factor beta (TGFβ), epidermal growth factor (EGF), hypoxia inducible factors (HIF) or Wnt signalling pathways, each of which have been implicated in fibrogenesis ( Richeldi et al, 2017 ; Yao et al, 2019 ; Martin-Medina et al, 2018 ; Königshoff et al, 2008 ; Yue et al, 2010 ; Bodempudi et al, 2014 ; Hill et al, 2019a ; Yao et al, 2021 ; Zhou et al, 2021 ). A prodrug form of the hypoxia mimetic and broad spectrum 2-oxoglutarate oxygenase inhibitor N-oxalylglycine (dimethyloxalylglycine, DMOG) ( Chowdhury et al, 2013 ), which inhibits the HIF prolyl hydroxylases with consequent stabilisation of HIF1α and HIF2α, most strongly upregulated both PLOD2 and LOXL2 mRNA and protein levels ( Figure 2a–c and Figure 2—figure supplement 1b ) but did not induce expression of interstitial collagen genes ( COL1A1 , COL3A1 ) ( Figure 2d and Figure 2—figure supplement 1c ).…”
Section: Resultsmentioning
confidence: 99%
“…To investigate common regulators of PLOD2 and LOXL2 in lung fibrosis, we studied their expression in primary human lung fibroblasts over a 72-hr time course following activation ( Figure 2—figure supplement 1a ) of transforming growth factor beta (TGFβ), epidermal growth factor (EGF), hypoxia inducible factors (HIF) or Wnt signalling pathways, each of which have been implicated in fibrogenesis ( Richeldi et al, 2017 ; Yao et al, 2019 ; Martin-Medina et al, 2018 ; Königshoff et al, 2008 ; Yue et al, 2010 ; Bodempudi et al, 2014 ; Hill et al, 2019a ; Yao et al, 2021 ; Zhou et al, 2021 ). A prodrug form of the hypoxia mimetic and broad spectrum 2-oxoglutarate oxygenase inhibitor N-oxalylglycine (dimethyloxalylglycine, DMOG) ( Chowdhury et al, 2013 ), which inhibits the HIF prolyl hydroxylases with consequent stabilisation of HIF1α and HIF2α, most strongly upregulated both PLOD2 and LOXL2 mRNA and protein levels ( Figure 2a–c and Figure 2—figure supplement 1b ) but did not induce expression of interstitial collagen genes ( COL1A1 , COL3A1 ) ( Figure 2d and Figure 2—figure supplement 1c ).…”
Section: Resultsmentioning
confidence: 99%
“…Most recently, Yao et al also showed that this event does not occur only in ATII cells first and in fibroblasts later but also in the reverse order, producing reciprocal paracrine signaling. They showed that both TGF-β-activated fibroblasts and IPF fibroblasts induce RAS activation in ATII cells, and this process is at least partially driven by the secreted protein acidic and rich in cysteine (SPARC), supporting the concept that aberrant bidirectional epithelial-mesenchymal crosstalk contributes to the development of a profibrogenic microenvironment, where a chronic wound-healing response leads to the development of lung fibrosis [44].…”
Section: The Role Of Bidirectional Epithelial-mesenchymal Crosstalk I...mentioning
confidence: 90%
“…As described above, cellular senescence plays a role in IPF lungs, but the mechanisms by which the senescence of ATII cells leads to IPF onset and progression have not been fully elucidated yet. As mentioned in the previous paragraph, senescent ATII cells acquire a phenotype called SASP, which is characterized by the secretion of proteins that affect nearby cells by promoting the activation of fibroblasts [44]. Among SASP factors, there are metalloproteinases (MMPs), such as MMP2 and MMP9, that belong to a family of zinc-dependent endopeptidases essential for ECM degradation and remodeling [49,70,71].…”
Section: The Role Of Ecm In Ipf Onset and Progressionmentioning
confidence: 99%
“…Myofibroblasts can also modulate epithelial apoptosis, preserving a pro-fibrotic environment [ 39 ]. As a result, bidirectional EMT cross-talk assists the pro-fibrogenic positive feedback loop, resulting in fibrosis progression rather than wound resolution [ 40 ]. AECs become “vulnerable and sensitive to apoptosis,” but myofibroblasts become “apoptosis-resistant and immortal” [ 41 ].…”
Section: Ctgf Maintains the Pro-fibrotic Environment In Ipfmentioning
confidence: 99%